Radiation nanosensitizers in cancer therapy-From preclinical discoveries to the outcomes of early clinical trials - Colette Bilynsky; Nadine Millot; Anne‐Laure Papa (Wiley, 2022)
Abstract Improving the efficacy and spatial targeting of radiation therapy while sparing surrounding normal tissues has been a guiding principle for its use in cancer therapy. Nanotechnologies have shown considerable growth in terms of innovation and the development of new therapeutic approaches, particularly as radiosensitizers. The aim of this study was to systematically review how nanoparticles (NPs) are used to enhance the radiotherapeutic effect, including preclinical and clinical studies. Clinicaltrials.gov was used to perform the search using the following terms: radiation, cancer, and NPs. In this review, we describe the various designs of nano‐radioenhancers, the rationale for using such technology, as well as their chemical and biological effects. Human trials are then discussed with an emphasis on their design and detailed clinical outcomes.